Cybrid Model Supports Mitochondrial Genetic Effect on Pig Litter Size - Liu, Hao; Wang, Jikun; Wang, Dan; Kong, Minghua; Ning, Chao; Zhang, Xing; Xiao, Jinlong; Zhang, Xin; Liu, Jianfeng; Zhao, Xingbo (Frontiers in Genetics, 2020)
In pigs, mitochondrial DNA (mtDNA) polymorphism and the correlation to reproductive performance across breeds and individuals have been largely reported, however, experimental proof has never been provided. In this study, we analyzed 807 sows for correlation of total number born (TNB) and mitotype, which presented the maximum of 1.73 piglets for mtDNA contribution. Cybrid models representing different mitotypes were generated for identification of the mtDNA effect. Results indicated significant differences on cellular and molecular characteristics among cybrids, including energy metabolic traits, mtDNA copy numbers and transcriptions, mRNA and protein expressions on mitochondrial biogenesis genes and reproduction-related genes. Referring to mitotypes, the cybrids with prolific mitotypes presented significantly higher oxygen consumption rate (OCR) productions, mtDNA transcriptions and copy numbers than those with common mitotypes, while both mRNA and protein expressions of PPARA, TFAM, ER1, ER2 and ESRRG in prolific cybrids were significantly higher than those with common mitotypes. Cybrid models reflected the mtDNA effect on pig litter size, suggesting the potential application of mtDNA polymorphism in pig selection and breeding practices.